Avaliação da aprendizagem: um estudo sobre a produção acadêmica dos Programas de Pós-Graduação em Educação (PUCSP, USP, UNICAMP) (2000 2007) - Uler, Arnilde Marta (2010)
The objective of this study was to document and comprehend the conception of the LEARNING EVALUATION spread in the academic production of master‟s degrees in three universities: Pontificia Universidade Católica de São Paulo PUC/SP, Universidade de São Paulo USP and Universidade Estadual de Campinas UNICAMP, in the period of 2000 to 2007. The exploration of the theoretical perspective was made through the selection of authors whose studies associate to the learning evaluation or to the teacher formation such as: Nóvoa (1991), Luckesi (1993), Abramowicz (1994), Sousa (1994), Abrecht (1994), Candau (1996), Freitas (1996), Demo (1999), Perrenoud (1999), Sacristán (2000), Bonniol (2001), Cappelletti (2001), Saul (2001), Vial (2001), Imbérnon (2002), among others. From the study of the State-of-art of the academic production, composed by doctorate thesis and master‟s degree dissertations about learning evaluation (2000-2007), 37 papers on learning evaluation produced in the post graduation programmes in education during the mentioned period were selected. I have elaborated a summary of each one of the found papers and, forthwith, the analysis of each dissertation and thesis considering the categories of analysis: learning evaluation in the continuous progression and cycles, learning evaluation in the public politics and learning evaluation in the scholastic practice. After this analysis, I have elaborated a synthesis-analytic study chart of each paper adopting as descriptions: identifying, objective, range, methodology, and the main contributions to the conception of learning evaluation. This research points to the accomplished investigations mostly aiming the Elementary School, but already demonstrating worries about the learning evaluation in the High School. Still, there is a tendency for the traditional learning evaluation, but also, there are works that point to a emancipated, continuous, formative proposal. The research has also mentioned Pontifícia Universidade Católica de São Paulo PUC/SP, considering its post graduation programme in Education, as having the highest number of works dedicated to the learning evaluation, fact already identified in the study of Souza in 1994